Marieke van Houte: Return Migration to Afghanistan. Moving Back or Moving Forward? - Rytter, Mikkel (Tidsskriftet Antropologi, 2018)
Marieke van Houte: Return Migration to Afghanistan. Moving Back or Moving Forward? Anmeldes af Mikkel Rytter